Issues faced by health staff in a conflict affected District : A case study in Vavuniya - Sri Bavanadarajah, S (My University, 2009)
A paucity of studies exists regarding human resource management in areas which are exposed to long term arm conflicts. This study explored some of the problems faced by the state health staff in conflict affected Vavuniya District. A qualitative study was conducted among government healthcare workers in Vavuniya District. Data were collected from 40 staff members using face to face interview with semistructured questionnaire as a general interview guide. The snow ball sampling method was used to gather the information. Eighty percent of the respondents were Tamils; 52.5 percent were females; 37.5 percent had accommodation in their own house and 10 percent were in the quarters provided by the government; 42.5 percent was not satisfied with their present accommodation facilities; 27.5 percent had been their accommodation within 01 km. from their work place. Around two third of staff told that prices of the food items are higher than other parts of the country; 30 percent used bottled water for drinking; 62.5 percent faced difficulties in checkpoints when travelling out of the district; 80 percent experienced delay in reporting for duty even an emergency due to strict security measures. About 52.5 percent of the staff are satisfied with their jobs; 65 percent had excessive workload and 60 percent complained that no facilities available for their recreation activities; 40 percent complained that availability of poor training facilities; 42.5 percent expressed that poor coordination and less team spirit in the working environment; 55 percent was allowed to participate in the decision .About 80 percent expressed their inability to look after their family members' requirements; 90 percent blamed the armed political groups for major threat to the safety; 50 percent expected risk allowance. Around half of the respondents suggested to remove all the barriers which are preventing normal working conditions and 47.5 percent requested efficient medical managers to this district for the ilpprovement; 45 percent suggested more staff to be appointed and 40 percent expressed their concern of peace in this country for overall development in human resource.